Size exclusion and reversed-phase high-performance liquid chromatography/UV for routine control of thermal processing of cows' and donkey milk major proteins - Carina Pinho (2012)
Cows' and donkey milks (raw and thermally processed) and respective whey were analysed for quantification of major proteins. Two different chromatographic approaches, size exclusion (SE-HPLC) and reversed-phase high performance liquid chromatography (RP-HPLC) both coupled to UV detection were used. Usefulness of these methods for routine control of the effect of thermal processing was evaluated. The external standard method was used to calibrate the SE-HPLC and RP-HPLC systems. Concerning quantification of beta-lactoglobulin (beta-lg), alpha-lactalbumin (alpha-la), lysozyme (lys), and total casein (cn), no significant differences between results obtained by SE-HPLC and by RP-HPLC (t-test, P>0.05) were observed for raw milks and whey. Heating of cows' milk promoted aggregation of denatured proteins as observed by SE-HPLC, whereas alpha-la and beta-lg from donkey milk were stable to thermal processing at 100 degrees C (5 min). Lys was quantified in donkey raw milk and whey however, in thermally processed donkey milk lys was denatured and could not be quantified by HPLC.